Biomonitoring of pesticide exposure in farming-intensive communities of the Western Cape: a study using human serum analysis and zebrafish toxicity assays for more comprehensive risk assessment - Tiya, Luthando Lukhanyo (Stellenbosch : Stellenbosch University, 2026)
Thesis (PhD)--Stellenbosch University, 2025.